Geometric morphometrics genetic diversity analysis, and DNA barcoding of Arius species in Laguna de Bay, Philippines - Santos, Brian S.; Quilang, JonasP (Quezon City Institute of Biology, College of Science, University of the Philippines Diliman, 2011)
Kanduli, a local name for fishes of the family Ariidae in the Philippines, is an economically important fish in the country. Two species of Kanduli, Arius manillensis and Arius dispar were sampled from Laguna de Bay. Of these two, A. manillensis is endemic and is found only in Laguna de Bay. Shape differences between A. manillensis and A. dispar and variation between populations of these species were determined using geometric morphometrics. Samples were obtained from Binangonan, Tanay and Calamba areas of Laguna de Bay.Shape differences between species and among specimens of different sites were significant, but the groups were difficult to differentiate due to high overlaps in CVA plots and low Mahalanobis distance-based correct classification percentages. Genetic diversity of A.manillensis was the assessed using the mitochondrial DNA control region.
Thesis (M.S.- Biology) --University of the Philippines Diliman
Keywords: Fishes -- Classification; Fishes -- Breeding -- Philippines -- Laguna de Bay (Laguna).